A long-term analysis of atmospheric black carbon MERRA-2 concentration over China during 1980–2019. (1st November 2021) - Cao, Shanshan; Zhang, Shiqing; Gao, Chanchan; Yan, Yuanyuan; Bao, Jiehuan; Su, Ling; Liu, Mengqing; Peng, Nana; Liu, Min
Abstract: Black carbon (BC), an important component of atmospheric aerosols, has a great influence on regional and global radiation balance, climate and human health due to its small particle size, large specific surface area and radiation forcing. The long-term variation of atmospheric BC over China during 1980–2019 was investigated through MERRA-2 reanalysis data. MERRA-2 BC generally presented a good correlation (average R = 0.61) with 852 monthly samples from ground-based observations at 64 stations around China. In recent 40 years, the annual-averaged atmospheric BC concentration derived from MERRA-2 reanalysis data was 1.10 ± 0.22 μg/m 3, with an average annual growth rate of 1.52%. The monthly BC concentrations showed a "U"-shaped trend. Based on the Mann-Kendall trend analysis, the BC concentration can be roughly divided into three stages: (1) the "low value" stage with slow growth rate (1.68%) (1980–1999, 0.91 ± 0.10 μg/m 3 ), (2) the fluctuating "median value" stage with high growth rate (4.44%) (2000–2007, 1.28 ± 0.13 μg/m 3 ), and (3) the "high value" stage with slow downtrend (−0.87%) (2008–2019, 1.32 ± 0.06 μg/m 3 ). Peak times and multi-year average growth rates of BC concentration and emission were not synchronized. The spatial distribution, dividing by the Hu Line, a line dividing the population density and urbanization of China, formed three BC high-value areas in Sichuan Basin, Northern Henan area and Beijing-Tianjin-Hebei (BTH). The altitude where the concentration of BC increased fastest at an average annual growth rate of 3.47% during 1980–2019 was between 0 and 500 m. The growth rate of BC concentration was close to zero as the altitude increased. During the past 40 years, significant overall uptrends were detected in MERRA-2 BC concentration with Mann-Kendall trend analysis at pixel scale, especially during 1980–1999 and 2000–2007. This increasing trend was more obvious in the eastern Hu Line. Whereas, a downward trend was appeared in the plains and basins of southeast China during 2008–2019. Highlights: MERRA-2 BC was validated with 852 ground-based samples at 64 stations over China. BC concentration divided by the Hu Line was high in the east and low in the west. Evident uptrends were detected during 1980–1999 and 2000–2007 with M-K method. A downtrend was arose in plains and basins of southeast China during 2008–2019.